2019
DOI: 10.3390/atmos10100621
|View full text |Cite
|
Sign up to set email alerts
|

Tailpipe VOC Emissions from Late Model Gasoline Passenger Vehicles in the Japanese Market

Abstract: High concentrations of tropospheric ozone remain a concern, and strategies to reduce the precursors of ozone, volatile organic compounds (VOCs) and nitrogen oxides, have been established in many countries. In this study, chassis dynamometer experiments were conducted for 25 late model gasoline passenger vehicles in the Japanese market to evaluate VOC emission trends. Tailpipe emissions were collected and analyzed using gas chromatography mass spectrometer and flame ionization detector, and liquid chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…The 76 components in the puff loss emissions were analyzed by a gas chromatography mass spectrometer and flame ionization detector (GC-MS/FID; GCMS-QP2020, Shimadzu Corporation, Kyoto, Japan). A detailed account of the experimental setup is provided in our previous study [25].…”
Section: Composition Of Vocsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 76 components in the puff loss emissions were analyzed by a gas chromatography mass spectrometer and flame ionization detector (GC-MS/FID; GCMS-QP2020, Shimadzu Corporation, Kyoto, Japan). A detailed account of the experimental setup is provided in our previous study [25].…”
Section: Composition Of Vocsmentioning
confidence: 99%
“…Thus, the seasonal effects on puff loss emissions are expected to be stable under constant ambient pressure conditions. Finally, according to Figure 6c, the puff loss emissions per refueling event from the tested vehicle in this study approximately ranged from 2 to 5 g. The annual average driving distance of passenger vehicles in Japan is approximately 10,000 km, based on a statistical study [29], and the fuel consumption of the tested vehicle is 11.2 L/100 km based on the worldwide harmonized light duty driving test cycle (WLTC), measured via the chassis dynamometer test (details on this test are described in one of our previous studies [25]). The size of the fuel tank is 70 L, and we assumed that refueling is done when the amount of fuel in the tank drops to 20 L. The number of gasoline vehicles in Japan is approximately 60 million [30].…”
Section: Sensitivity Analysis Of the Puff Loss Estimation Modelmentioning
confidence: 99%
“…Analyses of this type require researchers to optimize sample collection and determine an appropriate analytical method. A literature review showed that scientists use a number of available methods of collecting research material and chromatographic methods, i.e., GC-MS [6][7][8][9][10][11][12][13][14], LC-MS [15], TD-GC-MS [16] with sampling into sorbent tubes [14], feeding whole air or raw exhaust gases into Tedlar bags [9,[17][18][19][20][21][22][23], microextraction into the solid phase [24], or the flame ionization method [25][26][27]. In the work of other research centers [22,23], volatile organic compounds were collected from two-wheeled vehicles into a set of Tedlar bags.…”
Section: Introductionmentioning
confidence: 99%
“…This has been achieved by technological innovations such as three‐way catalysts and diesel particulate filters and by the efforts of automobile manufacturers. However, studies based on chassis dynamometer experiments have reported that catalyst performance is reduced at cold start and VOC emissions could be up to 30 times higher than in the case of hot start (Hata et al., 2019). Compared to stricter exhaust regulation, regulations for fuel evaporation VOCs are relatively lax, but measures are being strengthened.…”
Section: Introductionmentioning
confidence: 99%